FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI PEPAYA DI KECAMATAN WANAREJA KABUPATEN CILACAP - Junaedi, Faozan Bahar; Yusuf, Muhamad Nurdin; Kurnia, Rian (Universitas Galuh, 2024)
The research was carried out with the aim of knowing: (1) The factors that influence the production of papaya simultaneously or partially. The research was conducted using quantitative methods in Wanareja District, Cilacap Regency. By using the census method to take a sample of 34 people. Factors that affect papaya production were analyzed using multiple linear regression equations where parameter estimation was carried out using SPSS 25. The results showed that simultaneously the variables of land area, seeds, labor, organic fertilizers, inorganic fertilizers, and pesticides had an effect on production papaya. As for partially, the factors that have a positive and significant effect on papaya production are land area, organic fertilizers, and inorganic fertilizers. While seeds and labor have a positive but not significant effect on papaya production. The factors that have a negative or insignificant effect are pesticides on papaya production in Wanareja District, Cilacap Regency.